TANGGUNG JAWAB INVESTOR ASING DITINJAU DARI UNDANG-UNDANG PENANAMAN MODAL - Putra Thama, Aditya; Puspawati, I Gusti Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
The exposure of free market towards Indonesia had ease the access of foreign investor in conducting investment in Indonesia. However, during its application, both foreign and national investor shall be liable in order to gain optimal results for both the investor and Indonesia. This paper shall be composed to discover the liability of foreign investor pursuant to Law No 25 of 2007 concerning Investment. By applying the method of normative legal research and statutory approach, this writing shall enunciate Article 16 of respective law as the legal instrument in conducting the capital investment in Indonesia explicitly.
Keywords: Liability, Foreign Investor